Exploring economic empowerment and marginalization using data from developing countries - Bernasek, Alexandra, author; Bhattarai, Niroj, author; Brundage, Brenden, author; Miller, Ray, author; Mudenda, Lackson, author; Nguyen, Anh, author; Nugroho, Wisnu, author; Pena, Anita Alves, author; Sedai, Ashish, author; Shakya, Prasiddha, author; Thongngam, Arisa, author; Regional Economic Development Institute, publisher (Colorado State University. Libraries, 2021)
The Poverty Action Center is engaged in several ongoing data analyses to answer questions at the forefront of applied economics globally. Our Nepal team is examining links between migration and social mobility through the lens of caste/ethnicity and wealth accumulation using micro-data from the World Bank. This research contributes to understanding whether international migration allows marginalized groups to bypass labor market discrimination at home to advance economically. Our Haiti team is studying the effects of water, sanitation, and hygiene (WASH) on measures of women's empowerment (e.g., economic independence and decision-making) to link to the United Nation's Sustainable Development Goals of clean water and sanitation, good health and well-being, and gender equality. Our Ethiopia group is examining how water infrastructure and access in Ethiopia influences individual time use disaggregated by gender.